2017
DOI: 10.1016/j.bbapap.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Novel functions of CCM1 delimit the relationship of PTB/PH domains

Abstract: The study provides new insight into the structural characteristics of PTB/PH domains, essential structural elements of PTB/PH domain required for NPXY motif-binding, and function and relationship among PTB, PH and FERM domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 101 publications
(148 reference statements)
3
34
0
Order By: Relevance
“…CCM proteins have been demonstrated to play major roles in microvascular angiogenesis in human and animal models (1)(2)(3)(4)(5)(6), which is an essential step for cancer growth during tumorigenesis (5,6). Three genes have been identified as causes of CCMs: cerebral cavernous malformations 1 [(CCM1) also termed Krev interaction trapped 1 (KRIT1)], cerebral cavernous malformation 2 [(CCM2) also termed MGC4607] and cerebral cavernous malformation 3 [(CCM3) also termed programmed cell death 10 (PDCD10)].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCM proteins have been demonstrated to play major roles in microvascular angiogenesis in human and animal models (1)(2)(3)(4)(5)(6), which is an essential step for cancer growth during tumorigenesis (5,6). Three genes have been identified as causes of CCMs: cerebral cavernous malformations 1 [(CCM1) also termed Krev interaction trapped 1 (KRIT1)], cerebral cavernous malformation 2 [(CCM2) also termed MGC4607] and cerebral cavernous malformation 3 [(CCM3) also termed programmed cell death 10 (PDCD10)].…”
Section: Introductionmentioning
confidence: 99%
“…As one of three key components of the CSC, CCM3 was initially identified as a tumor-associated apoptotic protein (7) which directly interacts with CCM2 within the CSC complex (8,9), suggesting that the CSC complex may be involved in tumorigenesis. CCM1 is ubiquitously expressed in various cells and tissues (5,10); likewise, almost all expressed isoforms of CCM2 are ubiquitously expressed in various cells and tissues (11), providing additional evidence for the potential involvement of the CSC in diverse cellular events in health and diseases, including cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the three CCM proteins form the CSC, which plays an essential role in the pathogenesis of CCMs when disrupted [26]. Efforts to dissect CSC signaling cascades have been made (Additional file 11) [8,10,[20][21][22][23][24][25][26], but with some contradicting outcomes. It is essential to establish comparative omics methods to assess similarities among those independent studies, which can aid in identification of potential biomarker candidates for prognostic and diagnostic applications.…”
Section: Discussionmentioning
confidence: 99%
“…A comparative database in excel (Additional files 1 and 2) was set up for the nine total available CCM cohorts that were analyzed for our comparative omics studies [8,10,[19][20][21][22][23][24][25] (Fig. 1).…”
Section: Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation